Pengaruh Gaya Kepemimpinan Transformasional terhadap Tata Kelola Pembelajaran PAUD Di Kecamatan Cakranegara - Purnamasari, Tania; Nurhasanah; Sativa, Filsa Era (Mataram University, 2025)
This study focuses on examining the impact of transformational leadership style on early childhood education (PAUD) learning management in the Cakranegara region. The research employed a quantitative correlational method. The sample consisted of 51 randomly selected instructors, while the total population comprised 76 PAUD teachers. Data were collected using a closed-ended Likert-scale questionnaire. The data were analyzed using SPSS 25 through t-tests, simple linear regression, and Pearson correlation analysis. With a correlation coefficient of 0.773 and a significance level of 0.000, the findings demonstrate a strong relationship between learning management and transformational leadership style. Based on the results of the simple linear regression test, 59.7% of learning management is influenced by transformational leadership. The alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected, as the t-test shows a value of 8.517, which exceeds the t-table value of 1.676 with a significance level of 0.000 (< 0.05). These findings indicate that PAUD learning management in Cakranegara District is significantly influenced by transformational leadership.